Male meiosis in sweet cherry is constrained by the chilling and forcing phases of dormancy. (26th May 2020) - Fadón, Erica; Herrera, Sara; Herrero, María; Rodrigo, Javier
Abstract: Male meiosis in temperate fruit trees occurs in the anthers once a year, synchronized with the seasons. The alternation of dormant and growth cycles determines the optimum moment for the male gametophyte formation, a process sensitive to both cold and warm temperatures. This ensures pollen viability and subsequent reproduction success that guarantee fruit production. In this work, we explore how male meiosis is framed by seasonality in sweet cherry. For this purpose, the dormant phases, male meiosis and blooming dates were established in four cultivars with different flowering dates and chilling requirements over 7 years. The chilling and heat requirements for each cultivar were empirically estimated, and chilling and heat temperatures were quantified according to the Dynamic and Growing Degree Hours (GDH) models, respectively. Endodormancy was overcome approximately a fortnight earlier during the colder winters than during the milder winters. Against our initial hypothesis, these differences were not clearly reflected in the time of male meiosis. The period between chilling fulfillment and meiosis lasted several weeks, during which a high amount of GDH accumulated. Results showed that male meiosis is conditioned by endodormancy but especially by warm temperatures, during the forcing period. This differs from what has been described in other related species and creates a framework for further studies to understand the strategies of synchronizing dormancy with seasons.